Comparative Secretome Analyses of Trichoderma/Arabidopsis Co-cultures Identify Proteins for Salt Stress, Plant Growth Promotion, and Root Colonization - Rouina, Hamid; Tseng, Yu-Heng; Nataraja, Karaba N.; Uma Shaanker, Ramanan; Krüger, Thomas; Kniemeyer, Olaf; Brakhage, Axel; Oelmüller, Ralf (Frontiers in Ecology and Evolution, 2022)
Numerous Trichoderma strains are beneficial for plants, promote their growth, and confer stress tolerance. A recently described novel Trichoderma strain strongly promotes the growth of Arabidopsis thaliana seedlings on media with 50 mM NaCl, while 150 mM NaCl strongly stimulated root colonization and induced salt-stress tolerance in the host without growth promotion. To understand the dynamics of plant-fungus interaction, we examined the secretome from both sides and revealed a substantial change under different salt regimes, and during co-cultivation. Stress-related proteins, such as a fungal cysteine-rich Kp4 domain-containing protein which inhibits plant cell growth, fungal WSC- and CFEM-domain-containing proteins, the plant calreticulin, and cell-wall modifying enzymes, disappear when the two symbionts are co-cultured under high salt concentrations. In contrast, the number of lytic polysaccharide monooxygenases increases, which indicates that the fungus degrades more plant lignocellulose under salt stress and its lifestyle becomes more saprophytic. Several plant proteins involved in plant and fungal cell wall modifications and root colonization are only found in the co-cultures under salt stress, while the number of plant antioxidant proteins decreased. We identified symbiosis- and salt concentration-specific proteins for both partners. The Arabidopsis PYK10 and a fungal prenylcysteine lyase are only found in the co-culture which promoted plant growth. The comparative analysis of the secretomes supports antioxidant enzyme assays and suggests that both partners profit from the interaction under salt stress but have to invest more in balancing the symbiosis. We discuss the role of the identified stage- and symbiosis-specific fungal and plant proteins for salt stress, and conditions promoting root colonization and plant growth.